2022
DOI: 10.1007/s00394-022-02916-w
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation on an updated standardization of serum magnesium reference ranges

Abstract: Purpose Serum magnesium is the most frequently used laboratory test for evaluating clinical magnesium status. Hypomagnesemia (low magnesium status), which is associated with many chronic diseases, is diagnosed using the serum magnesium reference range. Currently, no international consensus for a magnesemia normal range exists. Two independent groups designated 0.85 mmol/L (2.07 mg/dL; 1.7 mEq/L) as the low cut-off point defining hypomagnesemia. MaGNet discussions revealed differences in serum magnesium referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 17 publications
2
33
0
5
Order By: Relevance
“…Half of the significant hypokalemias seem to be associated with magnesium deficiency; the co-administration of magnesium thus is essential in correcting serum potassium (K+) concentrations [ 27 ]. Enhanced gastrointestinal and renal excretion of K+ can also lead to hypokalaemia; however, it was shown that in patients with both hypomagnesemia and hypokalaemia, the repletion of Mg 2+ alone also increased the serum K+ level [ 4 , 28 ].…”
Section: Cardiovascular Importance Of Magnesiummentioning
confidence: 99%
See 3 more Smart Citations
“…Half of the significant hypokalemias seem to be associated with magnesium deficiency; the co-administration of magnesium thus is essential in correcting serum potassium (K+) concentrations [ 27 ]. Enhanced gastrointestinal and renal excretion of K+ can also lead to hypokalaemia; however, it was shown that in patients with both hypomagnesemia and hypokalaemia, the repletion of Mg 2+ alone also increased the serum K+ level [ 4 , 28 ].…”
Section: Cardiovascular Importance Of Magnesiummentioning
confidence: 99%
“…To date, monitoring magnesemia may be challenging, especially since there are no available standardized protocols for serum magnesium measurement in different patient populations or the general population. There are no evidence-based reference range values to date, but rather only a consensus-based cut-off value for defining hypomagnesemia, established at 0.85 mmol/L (2.07 mg/dL or 1.7 mEq/L) [ 4 ]. For serum measurement of Mg 2+ concentrations, the blood samples should be accurately prepared to avoid hemolysis since the magnesium stored in the erythrocytes exceeds serum magnesium [ 106 ].…”
Section: The Treatment Of Hypomagnesemiamentioning
confidence: 99%
See 2 more Smart Citations
“…B. 8-OH-dG) beitragen und fördert dadurch allgemein die zellulärer Seneszenz, die Atherogenese sowie die Alterung des kardiovaskulären Systems 34 35 36 37 38 39 .…”
Section: Altern Und Oxi-inflammageingunclassified